HYPERBOLIC EXPRESSIONS IN KODALINE’S ALBUM COMING UP FOR AIR - Wirandari, Rani Miftah (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
This study examines the types and meanings of hyperbole in Kodaline's album Coming Up for Air. The research analyzes 12 songs using Claridge’s (2011) theory to categorize the types of hyperbole and Leech’s (1989) framework to interpret their meanings. A qualitative research method was employed to conduct this study. This study being analyze by using Miles & Huberman (2014) interactive analysis model. The researcher categorizes the data analysis into three parts: data reduction, data visualization, and conclusion drawing and verification. The findings highlight the critical role of hyperbole in enhancing the emotional resonance of the lyrics, making them both relatable and memorable. These exaggerated expressions contribute significantly to Kodaline's unique, emotionally charged artistic identity, deeply engaging listeners and leaving a lasting impact. The result of this study is find 6 types of hyperbole on the 12 songs in Kodaline’s album Coming up for Air, there are single word, phrasal, clausal, superlative expressions, comparisons, and repetition hyperbole. This study also find the meaning of hyperbole using the theory by Leech’s (1989) on the 12 songs in Kodaline’s album Coming up for Air, there are conceptual, connotative, and affective meaning.